(untitled) (Research, Society and Development, 2021)
Reductive gastroplasty, also known as bariatric surgery, is recommended for patients with body mass index (BMI) > 40 kg/m2, regardless of the presence of comorbidities and BMI between 35 and 40kg/m2 if associated diseases presented. Bariatric surgeries can be divided into restrictive or mixed. The restrictive ones occur when only the stomach is modified. In mixed surgeries, there is a change in patient´s intestine and stomach. Both operations reduce the patient´s weight. This study sought to assess the remission of diseases such as systemic arterial hypertension, type two diabetes mellitus and dyslipidemia within five years after the operation and after this period in 53 patients of a gastroenterology clinic in west Parana. A reduction in the prevalence of all three studied pathologies was observed in the period up to five years after the operation (p<0,001) and after five years (p<0,001). Therefore, the effectiveness of bariatric surgery in reduction of the prevalence of diseases resulting from obesity is evident.